2019
DOI: 10.1186/s12877-019-1367-9
|View full text |Cite
|
Sign up to set email alerts
|

A bio-psycho-social approach for frailty amongst Singaporean Chinese community-dwelling older adults – evidence from the Singapore Longitudinal Aging Study

Abstract: BackgroundFew empirical studies support a bio-psycho-social conceptualization of frailty. In addition to physical frailty (PF), we explored mental (MF) and social (SF) frailty and studied the associations between multidimensional frailty and various adverse health outcomes.MethodsCross-sectional and longitudinal analyses were conducted using data from a population-based cohort (SLAS-1) of 2387 community-dwelling Singaporean Chinese older adults. Outcomes examined were functional and severe disability, nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 34 publications
(53 reference statements)
1
42
5
Order By: Relevance
“…The possible explanation could be that older people who had been living in a private institution (more expensive in the metropolitan areas than public institution) usually have higher social economic status; they were more likely to feel lonely [30] and loss of appetite [31] when staying away from family and changing their ways of previous life, resulting in higher likelihood of being frailer. Compared with people living with their partners in the same nursing home, those who live with alone or share the room with unknown person may become more frail because of poorer social ties [32] and mental disorders [33]. In line with previous studies [34,35], we also found that regular exercise was associated with physical frailty.…”
Section: Discussionsupporting
confidence: 89%
“…The possible explanation could be that older people who had been living in a private institution (more expensive in the metropolitan areas than public institution) usually have higher social economic status; they were more likely to feel lonely [30] and loss of appetite [31] when staying away from family and changing their ways of previous life, resulting in higher likelihood of being frailer. Compared with people living with their partners in the same nursing home, those who live with alone or share the room with unknown person may become more frail because of poorer social ties [32] and mental disorders [33]. In line with previous studies [34,35], we also found that regular exercise was associated with physical frailty.…”
Section: Discussionsupporting
confidence: 89%
“…While the prevalence of frailty was 30.7% in all participants, the prevalence was 35.0% for pre-frailty and 34.3% for robust. The prevalence of frailty in our study was relatively high compared with previous estimates, which ranged from 11% up to 26% in community samples (34)(35)(36), which may be attributed to our study design and that participants came from primary care clinics. Frailty and cognitive impairment are distinguishable facets of aging that interact in the cycle of age-related decline.…”
Section: Discussioncontrasting
confidence: 74%
“…The proportion of residents aged 65 and above has increased from 8.8% in 2009 to 14.4% in 2019 [24], and the prevalence of frailty ranges from 5.7-11.3% in the population [4], depending on the operationalization of frailty. Studies in Singapore established physical health determinants of frailty such as multimorbidity [4,[25][26][27][28], physical exercise [4], and other lifestyle factors, including smoking [29] and drinking [25,27]. Mental health determinants included cognitive impairment [4,27,28] and depressive symptoms [4, 25-27, 29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Singapore established physical health determinants of frailty such as multimorbidity [4,[25][26][27][28], physical exercise [4], and other lifestyle factors, including smoking [29] and drinking [25,27]. Mental health determinants included cognitive impairment [4,27,28] and depressive symptoms [4, 25-27, 29, 30]. However, compared to physical and mental domains, the social health domain is the least well studied, with social networks [27,28] and social activity [27], both of which evaluating the structural aspects of social health, found to be determinants of frailty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation